An aphid effector promotes barley susceptibility through suppression of defence gene expression. (28th January 2020) - Escudero-Martinez, Carmen; Rodriguez, Patricia A; Liu, Shan; Santos, Pablo A; Stephens, Jennifer; Bos, Jorunn I B
Abstract : Functional characterization of cereal pest effectors reveals virulence activities in barley, such as promoting barley susceptibility through suppression of defence and hormone signalling genes. Abstract: Aphids secrete diverse repertoires of effectors into their hosts to promote the infestation process. While 'omics' approaches facilitated the identification and comparison of effector repertoires from a number of aphid species, the functional characterization of these proteins has been limited to dicot (model) plants. The bird cherry-oat aphid Rhopalosiphum padi is a pest of cereal crops, including barley. Here, we extend efforts to characterize aphid effectors with regard to their role in promoting susceptibility to the R. padi– barley interaction. We selected three R. padi effectors based on sequence similarity to previously characterized Myzus persicae effectors and assessed their subcellular localization, expression, and role in promoting plant susceptibility. Expression of R. padi effectors RpC002 and Rp1 in transgenic barley lines enhanced plant susceptibility to R. padi but not M. persicae, for which barley is a poor host. Characterization of Rp1 transgenic barley lines revealed reduced gene expression of plant hormone signalling genes relevant to plant–aphid interactions, indicating that this effector enhances susceptibility by suppressing plant defences in barley. Our data suggest that some aphid effectors specifically function when expressed in host species, and feature activities that benefit their corresponding aphid species.